2015
DOI: 10.4317/medoral.20009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-alveolar placement of 0.2% chlorhexidine bioadhesive gel on the incidence of alveolar osteitis following the extraction of mandibular third molars. A double-blind randomized clinical trial

Abstract: Alveolar osteitis (AO) is a common complication after third molar surgery. One of the most studied agents in its prevention is chlorhexidine (CHX), which has proved to be effective. Objectives: The aim of this randomized double-blind clinical trial was to evaluate the efficacy of 0.2% bioadhesive chlorhexidine gel placed intra-alveolar in the prevention of AO after the extraction of mandibular third molars and to analyze the impact of risk factors such as smoking and oral contraceptives in the development of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 21 publications
2
28
1
7
Order By: Relevance
“…However, a study done by Rubio-Palau showed there was a significant reduction of AO incidence in the intervention group (22.22% times compared with the control group) [19]. …”
Section: Resultsmentioning
confidence: 99%
“…However, a study done by Rubio-Palau showed there was a significant reduction of AO incidence in the intervention group (22.22% times compared with the control group) [19]. …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 21 articles were browsed according to the inclusion criteria. Finally, 11 articles (Torres‐Lagares et al , ,b; Hita‐Iglesias et al , ; Babar et al , ; Haraji et al , ; Haraji and Rakhshan, , ; Rubio‐Palau et al , ; Freudenthal et al , ; Jovanovic et al , ; Requena‐Calla and Funes‐Rumiche, ) were adopted for final analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the 11 primary studies (Torres‐Lagares et al , ,b; Hita‐Iglesias et al , ; Jovanovic et al , ; Babar et al , ; Haraji et al , ; Haraji and Rakhshan, , ; Freudenthal et al , ; Rubio‐Palau et al , ; Requena‐Calla and Funes‐Rumiche, ) are listed in Table . The publication year varied from 2006 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations